A ação civil ex delicto, a defesa dos direitos constitucionais da personalidade e os meios de prova - Barbosa, Bruno Loiola (2015)
The work investigates civil action ex delicto, and the various problems of the current system, with different approaches. The broad scope cover many problems, which violate various constitutional commands, both implicit as explicit, such as the reasonable duration of the process and the prohibitions of proof. The aim of this study is to investigate how the current Brazilian system of civil actions ex delicto works and determine which measures are possible to be performed, in this constitutional order, to increase the efficiency and effectiveness of such the system. Furthermore, we idealize a hybrid system process in order to avoid discrepancies. The evidence system will be widely studied because it is a critical point in the systems convergence. The methodology used was the doctrinal and jurisprudential research of Brazilian law. In the context of comparative law was made a broad survey of American jurisprudence on their evidence system to obtain a moldable reference to the Brazilian constitutional system, given the fact that many of our principles are identical and that the discussions of the Supreme Court of the United States are extremely prolific due to the lack of legislation in most cases. The result, as was expected given the lack of legislative technique to unify two completely separate processes, is the existence of a true doctrinal and jurisprudential chaos, with numerous conflicting opinions on the numerous legislative vacancies. The conclusion is that you need to modify the system and makes it simpler by unifying processes and uniting all procedures in a hybrid system that is more efficient and does away with the injustice it happens when the victim may be waiting decades to maybe get tiny amounts of money as "repair" or lawsuits with different results.